2001
DOI: 10.1023/a:1011857802317
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present review of the literature on mites of the genus Chorioptes Gervais and Van Beneden, 1859 argues for a support of the validity of C. bovis (Hering, 1845) and C. texanus Hirst, 1924 based on biological, morphological and molecular genetic studies. However, the validity of three further species. C. crewei Lavoipierre, 1958, C. mydaus Fain, 1975 and C. panda Fain and Leclerc, 1975, is regarded as questionable because discriminations of mites, which were described as isolated cases only, were based on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In addition, the authors of a recently published paper on the behavior of cows with chorioptic mange on a dairy farm in British Columbia, Canada [5], provided skin scrapings for the speciation of the mites. The taxonomy of the genus Chorioptes has been repeatedly a matter of debate in the recent past [8][9][10]. The most recent revision concluded that there are six valid species including C. bovis (Hering, 1845) and C. texanus Hirst, 1924 which are the causative agents of chorioptic mange in bovines and other ungulates [1].…”
Section: Source Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the authors of a recently published paper on the behavior of cows with chorioptic mange on a dairy farm in British Columbia, Canada [5], provided skin scrapings for the speciation of the mites. The taxonomy of the genus Chorioptes has been repeatedly a matter of debate in the recent past [8][9][10]. The most recent revision concluded that there are six valid species including C. bovis (Hering, 1845) and C. texanus Hirst, 1924 which are the causative agents of chorioptic mange in bovines and other ungulates [1].…”
Section: Source Of Materialsmentioning
confidence: 99%
“…However, a generally higher level of restlessness, especially during the milking process, or an increase in activities to relieve pruritus associated with mange, constitute long-term stressors which reduce the well-being of the animals and can contribute to productivity losses [2][3][4][5][6][7]. The taxonomy of the genus Chorioptes has been repeatedly a matter of debate in the recent past [8][9][10]. The most recent revision concluded that there are six valid species including C. bovis (Hering, 1845) and C. texanus Hirst, 1924 which are the causative agents of chorioptic mange in bovines and other ungulates [1].…”
Section: Introductionmentioning
confidence: 99%
“…crewei and Ch. mydaus were considered dubious (Zahler et al, 2001;Wang et al, 2012;Suh et al, 2008) and Ch. sweatmani was suspected based on data of molecular and morphometry studies, but not properly described (Hestvik et al, 2007;Lusat et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…texanus from both domestic and wild animals, including goats in Texas, reindeer in Canada, cattle in Brazil, Israel, Germany, and the United States, and moose in Poland. Also, this species of Chorioptes was isolated from cattle and goats in Southeast Asian countries, Japan and Malaysia, as well as from Holstein cattle in Korea (Dorny et al, 1994;Nagata et al, 1995;Zahler et al, 2001;Suh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Itching also makes the animal restless and can result in reduced production of beef and milk [1012]. Based on morphological, epidemiological and genetic differentiation, Chorioptes bovis and Chorioptes texanus are generally accepted as two distinct valid species [1, 13, 14]. The egg, larva, protonymph, deutonymph and adult constitute a single life-cycle which spans approximately three weeks [7, 15].…”
Section: Introductionmentioning
confidence: 99%